Studi Kinetika Reaksi Pada Proses Deasetilasi Kitin Dari Limbah Industri Ebi - Jenial S; Ahmad Fadli; Yelmida Aziz (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Chitosan is used in a variety of industrial applications, such as purification agents, flocculation agents, anti-microbial agents, biological adhesives, anti-tumor agents and the cosmetic industry. This study studied deacetylation reaction kinetics and the effect of particle size difference on chitosan formation of chitin using raw materials of ebi industrial waste. Chitosan was obtained by deproteination, demineralization and deacetylation using 50% NaOH with a ratio of 1:20 (w / v) at a temperature of 80 ° C. Samples were analyzed using FTIR sprestroscopy and acid-base titration. The results showed the deacetylation degree at minute 120 for chitin diameter 0.25, 0.177, 0.152 mm were 51.51, 64.39, and 78.87%, respectively. The reaction mechanism is determined by model matching using the SSE value of the model against the value of the data obtained. From the result of approach done using the Shrinking Unreacted Core model it is known that the reaction is influenced by diffusivity. This corresponds to the value of the obtained diffusivity for each sample ranging from 0.25, 0.177 and 0.152 mm diameters respectively of 1.841. 10-18, 2.657. 10-18, and 3.085 .10-18 m2/s.Keywords : Deacetylation, reaction kinetics, chitosan, ebi’s waste, shrinking unreacted core model